Meta-Analysis of the Effect of Aerobic Exercise Combined with Respiratory Training on Stable Chronic Obstructive Pulmonary Disease - Nixi Huang; Lina Peng; Hongjie Li; Juncheng Si; Lei Shi; Yu Wang; Jiangrui Liao; Lili Sun (COPD)
Purpose: The purpose of this study was to conduct a meta-analysis of the effects of aerobic exercise combined with respiratory training on patients with stable chronic obstructive pulmonary disease (COPD). Methods: The data of randomized controlled trials on the effects of aerobic exercise combined with respiratory training on patients with stable COPD published up to March 2024 were retrieved from six electronic databases (PubMed, Web of Science, Cochrane Library, Embase, CNKI and China Science and Technology Journal Database). The risk of bias and quality of evidence were assessed using the Cochrane Collaboration tool, and the Physiotherapy Evidence Database (PEDro) Scale approach, respectively. Results: A total of 9 eligible trials with 449 patients with stable COPD were identified. The quality of evidence was moderate. Compared with the control group, the meta-analysis of aerobic exercise combined with respiratory training revealed a significant improvement in the St. George’s Respiratory Disease Questionnaire (SGRQ) score (standardized mean difference) (SMD=-0.68, 95% CI [-0.98, −0.39], p < 0.0001), 6-minute walking distance (6MWD) (standardized mean difference) (SMD = 0.84, 95% CI [0.58, 1.11], p < 0.00001), and exercise time (mean difference) (MD = 2.45, 95% CI [0.46, 4.44], p = 0.02). Moreover, aerobic exercise combined with respiratory training improved the secondary outcome measures. These included the modified Medical Research Council dyspnea Scale (mMRC) (SMD=-0.89, 95% CI [-1.32, −0.46], p < 0.00001), Chronic Respiratory Disease Questionnaire (CRQ) (MD = 1.43, 95% CI [-0.56, 3.41], p = 0.16). Conclusion: The results showed that this combination therapy significantly improved the patient’s exercise endurance, effectively alleviated the symptoms of dyspnea, and significantly improved the patient’s health-related quality of life.